Critical Discourse Analysis of “The Last Airbender”: A Portrayal of Cultural Genocide in Avatar - Aslam, Zunaira; Aqdas, Shayan (International Journal of Language and Literary Studies, 2024)
This paper aims to examine the textual and linguistic features used in the portrayal of genocide in the television series “Avatar: The Last Airbender,” which was released in 2005. It also analyzes the power structures present in the language of the characters. The analysis is based on the concepts of Fairclough’s Critical Discourse Analysis as he asserts that language is a form of social practice, and these discursive practices are ideologically motivated which legitimizes the production and reproduction of unequal power relations. The results of the study indicate the asymmetrical power relations and the narrative of cultural genocide in the discourse of the characters.